Memory performances and personality traits in mothers of children with obstructive sleep apnea syndrome - Smirni, Daniela (Psychol Res Behav Manag, 2019)
BACKGROUND: Chronic diseases in pediatric age have been identified as stressful risk factors for parents. Studies on caregivers have documented the impact of chronic parenting stress on emotion and cognition. AIM: To investigate the differences between a group of mothers of children affected by obstructive sleep apnea syndrome (OSAS) for at least 4 years and a group of mothers of typically developing children (TDC) in relation to parental stress, self-esteem, locus of control, and memory performances. METHODS: A group of 86 mothers (mean age 35.6±4.9, ranged between 32 and 41 years) of children with OSAS diagnosis, and a group of 52 mothers of TDC (mean age 35.9±4.2, ranged between 32 and 41 years) participated in the study. All participants were administered stress level, global self-esteem, internal/external locus of control scales, and memory assessment. RESULTS: Mothers of OSAS children, compared to mothers of TDC, had a significantly higher level of stress, lower self-esteem, more external locus of control and poorer memory performance. CONCLUSIONS: The child respiratory disease, with its sudden and unpredictable features, appeared as a significant source of stress for the mother. Such stress condition may have an impact on mothers’ personality traits (self-esteem, locus of control) and on their memory performances. The data have suggested a need for psychological support programs for mothers to better manage stress associated with children’s respiratory disease.